Balloon-assisted coiling of cerebral aneurysms with the dual-lumen Scepter XC balloon catheter: Experience at two high-volume centers. Issue 4 (August 2019) - Wallace, Adam N; Samaniego, Edgar; Kayan, Yasha; Derdeyn, Colin P; Delgado Almandoz, Josser E; Dandapat, Sudeepta; Fease, Jennifer L; Thomas, Mary; Milner, Anna M; Scholz, Jill M; Ortega-Gutiérrez, Santiago
Background: The Scepter XC is a dual-lumen balloon catheter that accommodates a 0.014-inch microwire and can be used for balloon-assisted coiling of cerebral aneurysms. We describe our experience with the use of this device. Methods: Two high-volume institution neurointerventional databases were retrospectively reviewed for cerebral aneurysms treated with balloon-assisted coiling using the Scepter XC balloon catheter. Patient demographics, aneurysm characteristics, and procedural details were recorded. Major procedure-related neurologic complications were defined as events that caused an increase in modified Rankin Scale that persisted for more than 1 week after the procedure. Follow-up aneurysm occlusion was assessed using the Raymond-Roy classification. Results: During the study period, 231 aneurysms were treated in 219 patients (152 women, 67 men) with a mean age of 58.4 ± 12.2 years. Mean aneurysm size was 6.1 ± 3.1 mm, with a mean neck diameter of 3.1 ± 1.3 mm. In total, 77.5% of aneurysms were wide necked, and 39.8% were treated in the setting of subarachnoid hemorrhage. The major complication rate was 0.9% (2/231) per treated aneurysm, including one stroke and one death related to intraoperative aneurysm rupture. Excluding patients who died, angiographic follow up was available for 85.3% (191/224) of aneurysms. During a mean follow up of 17.4 ± 13.0 months (range, 1.7–66.5 months), Raymond-Roy 1 and 2 occlusion rates were 56.5% (108/191) and 35.6% (68/191), respectively. The retreatment rate was 12.6% (24/191). Conclusion: Our experience using the coaxial dual-lumen Scepter XC for balloon-assisted coiling demonstrates acceptable aneurysm occlusion and complication rates.